Wireless Mobile Computing using Energy-E Client Caching - Gothwal, Mamta Gothwal; Kaur, Sukhwinder (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
Caching can reduce the bandwidth requirement in a mo-bile computing environment. However, due to battery power limitations, a wireless mobile computer may of-ten be forced to operate in a doze or even totally dis-connected mode. As a result, the mobile computer may miss some cache invalidation reports broadcasted by a server, forcing it to discard the entire cache contents after waking up. In this paper, we present an energy-e cient cache invalidation method, called GCORE, that allows a mobile computer to operate in a discon-nected mode to save battery while still retaining most of the caching bene ts after a reconnection. We present an e cient implementation of GCORE and conduct simulations to evaluate its caching e ectiveness. The results show that GCORE can substantially improve mobile caching by reducing the communication band-width (or energy consumption) for query processing.